Sistem Pembentukan Karakter di Pondok Pesantren Daarul Haliim Bandung - Ageng Saepudin Kanda; Nifal Nur`aida (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Boarding School (Pondok Pesantren) is the forerunner of Islamic educational institutions in Indonesia. The early presence of boarding schools is estimated from 300-400 years ago and reaches almost all levels of Indonesian Muslim community, especially in Java. Pesantren is a unique educational institution. Not only because of its very long existence, but also because of the culture, methods, and networks applied by the institution. After Indonesia gained its independence, especially since the transition to the New Order and when economic growth really rose sharply, pesantren education became more structured and the curriculum of pesantren became better. For example, in addition to the religious curriculum, pesantren also offers general subjects by using a dual curriculum, the curriculum of mone and the Kemenag curriculum. As an educational institution, pesantren is very concerned in the field of religion (tafaqquh fi al-din) and the formation of the character of the nation characterized akhlakul karimah . The provisions on religious education is described in the Law Sisidiknas Article 30 paragraph (4) that religious education in the form of education diniyah, boarding School, and other similar forms. The existence of pesantren is an ideal partner for government institutions to jointly improve the quality of education and the foundation of the nation's character. This can be found from various phenomena that occur such as brawl between schools and widespread distributors and users of drugs among young people rarely found they are boarding children or graduates from boarding schools. Therefore pentren as the basis for the implementation of social transformation through education to provide qualified human resources and morals karimah.